Associação entre o uso de medicamentos e os fatores de risco para queda em idosos portadores de doenças crônico degenerativas atendidos no Pronto Atendimento de um Hospital Universitário público referência no noroeste do Paraná - Silva, Josy Anne (2016)
The increase in the elderly population is a relevant fact and that requires attention. Among the diseases that contribute to decreased health conditions / disease of the elderly there are the falls, as the first cause of accidents in people aged 60 or more. Falls are a major public health problem, by its frequency, morbidity and high social and economic costs resulting from injuries. The aim of this study was to associate the use of medicines and the main reasons of falls in elderly patients in the emergency care units of a public reference hospital trauma care. This is a cross-sectional, retrospective, quantitative study with secondary data, in the year 2014. The medical records of elderly people were analyzed, patients with chronic degenerative diseases, fall victims, members of the emergency service, aged over 60 years . Data were collected using a questionnaire, later typed in Excel 2010 software, coded and analyzed. There were a total of 861 assistance per falling. Thun, they were analyzed the medical records of 234 individuals who had the criterion to remain under observation and / or hospitalized for 24 hours or more in the hospital, with hospital admission Authorization. It was observed, the prevalence of falls in the age group between 60 to 70 years 97 (41.5%) and frequently female 146 (62.4%). The participation in activities at home was present in 70 (29.9%) of records. The place of the falling with more frequency records was at home 183 (78.2%), with the reason to fall from height 173 (73.9%). The ISTCE (Integrated Service Trauma Care and Emergency) was the form of help most used by the elderly 88 (37.6%), but there was a high number brought by family 79 (33.7%) and 67 (28.7 %) were conducted by other forms of help. In relation to risk classification 132 (56.4%) elderly were classified in yellow, whose service should be carried out within twenty minutes. Only 4 (1.7%) elderly received immediate care and are classified in red, ie, with risk. Most of the victims belonged to municipality of Maringa 177 (75.6%). A large number of elderly patients remained hospitalized for more than 72 hours 85 (36.3%). They received sedation in hospital 195 (32%) older after the initial medical care. In the analysis of the consequences of the fall, it was observed that the traumatic brain injury mild or moderate was the major 62 (26.5%), followed by fractures of the upper limbs in 57 (24.4%) of the elderly, and fractures of the lower limbs in 52 (22.2%). Fractures of the lower limbs, 34 (65.4%) corresponds to femur fractures. Of the 234 patients, 119 (50.9%) were hospitalized waiting by surgery, these 83 patients (69.7%) were transferred to other hospitals. As for risk factors for fall, it was found that 175 (74.8%) had visual or hearing problems and chronic disease was present in 152 (64.95%) elderly. Of chronic diseases prevailed hypertension in 64 (27.4%) of the elderly, stroke and / or circulatory disease in 11 (4.7%) elderly and psychiatric disorders in 10 (4.3 %). The alcohol use was found in 21 (9.0%) records. Most falls occurred in the afternoon 97 (41.5%). Register of previous falls were present in only 7 (3%) of records. In relation to commitment of the members and difficulty muddle it was found in 14 (6.0%). The use of continuous medication appeared in 226 (96.6%) records, whereas chronic disease was registry in 152 (64.9%). The use of medication without prescription appeared in 87 (38.5%) records. Of those who were using medication 39 (16.7%) used only one, 27 (11.5%) two drugs and 23 (9.8%) three drugs. Antihypertensive drugs were the most commonly used by the elderly 124 (53.0%), followed by anti-diabetic 36 (15.4%) and diuretics (33%). The study showed that the fall is a frequent mechanism of trauma in the elderly and causing injuries that vary in severity. It showed a high number of elderly people who used continuous medication but did not have the information of having chronic disease and that, as polypharmacy may be associated with vulnerability of the elderly to fall. A fall is related to a number of factors risk, so it is important to recognize the causal agents for the targeting of preventive and care actions.